Dinamika Tingkat Kecukupan Pangan Di Kabupaten Subang Jawa Barat - Harini, Rika; Dike Alma Dian Prastika; Fidiatun Nofus (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Food problems are still a hot issue on the agenda in various countries in the world. This is the basis for determining SDGs in goals 2 and 12, namely eliminating hunger and balanced consumption and production. As a basic human need to live, food availability is a top priority in overcoming food shortages. The increase in population has caused a decrease in the area of ​​agricultural land as a producer of food. The impact that arises is a decrease in agricultural production, thus threatening the level of food sufficiency. The purpose of this study is to examine and analyze the trend of agricultural land carrying capacity and to analyze the spatial level of rice food sufficiency in Subang Regency in 2019-2023. The research method was carried out descriptively quantitatively based on secondary data analysis. There are 3 categories of agricultural land carrying capacity (1, 2 and 3). Around 83% (25 sub-districts) in Subang Regency are included in category 1 or high agricultural land carrying capacity and around 13-16% (4-5 sub-districts), the carrying capacity level is medium and low. The level of food sufficiency is known by knowing the amount of rice availability in each sub-district. Spatially and temporally presented with a map with the results that there is a positive correlation between the carrying capacity of agricultural land and the level of rice food sufficiency. Districts with high agricultural land carrying capacity have a high food sufficiency index (rice availability is surplus) and vice versa. The area of ​​agricultural land and the area of ​​harvest are the main factors in determining the high and low carrying capacity of agricultural land and the level of rice food sufficiency.